Modulation of Digestive Enzyme Activities and Intestinal γ-Proteobacteria in Gilthead Sea Bream Fed High-Fat Diets Supplemented with HIDROX® Olive Oil Extract - Irene García-Meilán; Sara Balbuena-Pecino; Manel Montblanch; Sara Ramos-Romero; Ramón Fontanillas; Joaquim Gutiérrez; Encarnación Capilla; Isabel Navarro; Ángeles Gallardo (Animals, 2025)
High-fat diets are commonly used in fish farming due to their protein-sparing effect, contributing to reduced production costs. However, this practice may have adverse effects such as metabolic impairment and inflammation. These problems can be assessed in two ways: by developing functional diets or using food restriction, which leads to compensatory growth. The present study characterized digestion in gilthead sea bream fed a high-fat diet in the presence (HT) or absence (HF) of an olive oil polyphenol as an additive, hydroxytyrosol, under two different dietary regimes: feeding to satiation (ST) or at a 40% restriction (R). Digestive enzyme activities, specifically trypsin-like activities, were mainly upregulated by dietary treatment (HT). In contrast, restriction effects mainly appeared during digestion in the pyloric caeca, where a significant rise in chymotrypsin-like activities was detected. Moreover, those fish tended to have an increased relative intestinal length compared to those fish fed at a standard ration. Feed restriction enhanced the growth of γ-Proteobacteria in pyloric caeca and proximal intestinal regions, without altering their population in the distal intestine. Overall, it is suggested that hydroxytyrosol inclusion at a standard ration could improve digestion processes in gilthead sea bream fed high-fat diets under healthier conditions than without this additive.